Emerging Implications of Serum Resolvin D2 as a Biochemical Marker for Severity Assessment and Prognosis Prediction Following Moderate-Severe Traumatic Brain Injury: A Prospective Cohort Study - Zong H; Zong Y; Li J; Zhao S; Wu W; Chen R; Zhao G; Li Z (Neuropsychiatric Disease and Treatment)
Hua Zong,* Yaqiong Zong,* Jian Li, Shaoyun Zhao, Weipeng Wu, Runhong Chen, Guoan Zhao, Zhuolun Li Department of Neurosurgery, Changzhi People’s Hospital, Changzhi, Shanxi Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian Li, Department of Neurosurgery, Changzhi People’s Hospital, Changzhi, Shanxi Province, People’s Republic of China, Email lijian958801@163.comBackground: Resolvin D2 (RvD2), which exhibits anti-inflammatory properties, is neuroprotective. This study aimed to ascertain the potential of serum RvD2 level as a prognostic predictor of moderate-to-severe traumatic brain injury (msTBI).Methods: In this prospective cohort study, serum RvD2 levels were measured in 136 patients with msTBI and 100 healthy controls. The severity scoring systems encompassed the Rotterdam computed tomography classification and Glasgow Coma Scale (GCS). Post-trauma six-month Glasgow outcome scale (GOS) was deemed an outcome indicator, with GOS scores below 4 indicating poor prognosis. Sequential univariate and multivariate analyses were used to determine the correlative factors of changeable serum RvD2 levels and the predictors of adverse prognosis.Results: Patients displayed a marked decline in serum RvD2 levels compared to controls (median, 95.2 versus 252.8 pg/mL; P< 0.001). Serum RvD2 levels were independently correlated with GCS scores (beta, 8.989; 95% confidence interval (CI), 3.678– 14.280; P=0.001) and Rotterdam scores (beta, − 14.676; 95% CI, − 25.885--3.468; P=0.011), and were independently associated with continuous GOS scores (beta, 0.004; 95% CI, 0.002– 0.007; P=0.003), ordinal GOS scores (odds ratio, 1.008; 95% CI, 1.002– 1.015; P=0.015), and poor prognosis (odds ratio, 0.991; 95% CI, 0.983– 0.999; P=0.037) at the six-month mark. A linear correlation was observed between serum RvD2 levels and the likelihood of poor prognosis (P for nonlinear = 0.090). Serum RvD2 levels exhibited strong discrimination efficiency for the probability of poor prognosis (P< 0.001), with similar ability as Rotterdam scores (P=0.337) and GCS scores (P=0.300). The integrative model encompassing serum RvD2, Rotterdam scores and GCS scores performed well using a series of statistical methods.Conclusion: A significant decrease in serum RvD2 levels after msTBI may accurately indicate trauma severity and efficiently distinguish the possibility of poor neurological outcomes in msTBI, signifying that serum RvD2 may be of clinical significance in the prognostic prediction of TBI.Keywords: resolvin 2, traumatic brain injury, prognosis, severity, biomarkers